Moving centre stage : the changing role of the non-executive director - Gay, Keith (2000)
Seeks to answer the question how non-executive or independent directors have improved corporate governance in the UK. Describes some of the key findings of a series of interviews witn non-executive directors which took place between January and March 2000.